Measurements of traditional Chinese medicine health literacy regarding chronic pain: a scoping review - Zhiyi Qian; Grace Y Wang; Marcus Henning; Yan Chen (BMC Complementary Medicine and Therapies)
Abstract Chronic pain is a prevalent health condition that imposes a significant burden on the global health system. Health literacy is a determinant of the quality of pain management which directly impacts public and individual health. However, the existing health literacy measurements have predominantly focused on medical models stemmed from Western culture and the knowledge of non-Western health models has largely been neglected. This review scopes refereed health literacy publications with regard to traditional Chinese medicine and chronic pain to explore and identify 1) the conceptual basis underlying the development of traditional Chinese medicine health literacy in this area, and 2) measurement tools used in this area and their associated psychometric qualities. Twenty-eight journal articles were assessed and the results showed that most studies’ conceptual frameworks were unable to cover three key health literacy aspects defined by the World Health Organization (access, understand, and apply). Furthermore, the identified health literacy measurement tools generally lacked rigorous psychometric evaluation. Future studies should focus on exploring a comprehensive model that encompasses various health models and developing measurement tools with more culturally representative psychometric assessments.